2020
DOI: 10.1177/0957650920950085
|View full text |Cite
|
Sign up to set email alerts
|

Unscented Kalman filtering method for scheduling photovoltaic power generation system fluctuations

Abstract: For the intermittent nature of renewable resources (such as wind and solar), smooth power fluctuations are required before the energy conversion system can be injected into the grid. The battery system is a typical smoothing control method for photovoltaic power. The long-term overcharge and overdischarge make the battery energy storage scheme unattractive. In this paper, the output power fluctuation of the photovoltaic power generation system is smoothed based on the unscented Kalman filter (UKF) method combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…(2) DC bus topology Different power generation units are connected to the public bus in the form of DC, through which the bus supplies power to the DC load and ac users [11,12]. The topology of the DC bus is shown in Figure 3.…”
Section: Design Of Optimization Scheduling Methods Of Solar Photovolt...mentioning
confidence: 99%
“…(2) DC bus topology Different power generation units are connected to the public bus in the form of DC, through which the bus supplies power to the DC load and ac users [11,12]. The topology of the DC bus is shown in Figure 3.…”
Section: Design Of Optimization Scheduling Methods Of Solar Photovolt...mentioning
confidence: 99%
“…The results showed that in a properly designed perovskite structure with multi-layer slender metal nanoparticles, the absorption of photons can be increased and the binding energy of excitons can be reduced at the same time. Thus, the efficiency can be improved through metallization, which cannot be achieved in traditional p-n junction batteries [8]. To achieve efficient photovoltaic power generation prediction in smart city energy management, Sun et al studied and designed a model based on a multi-scale short-term memory recurrent neural network that can predict very short-term photovoltaic power generation.…”
Section: Related Workmentioning
confidence: 99%
“…When C is 0, the switch is open; when C is 1, the switch is closed. D is calculated using Equation (8).…”
Section: Construction Of the Mppt Control Algorithm Based On Hqpsomentioning
confidence: 99%
“…Hence, the most important challenge is making these microgrids efficiently cooperate and exchange power in case of system resilience [15]. Hence, this paper addresses this issue to smooth the progress of the DES' implementation [16], [17]. The principle of the multiagent system (MAS) has gained more use in recent years even for the management of centralized power systems or of the decentralized management and control strategy for distributed microgrids [18]- [20].…”
Section: Introductionmentioning
confidence: 99%